A CASE REPORT: THE STRATEGY OF CORNEAL ULCERS - Kuswaya Waslan; Rahayu Oktaliani (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
Introduction: Corneal ulcers are considered an ophthalmologic emergency because of their potential to permanently impair vision or perforate the eye. Accurate and quick diagnosis and prompt treatment is a key to improve clinical and visual outcomes in cases of corneal ulceration. In case of medical treatment failure, resulting in ulcer perforation, surgical care is required. Here we make an attempt to provide an overview on diagnostic approach and management protocol of corneal ulcer. Case Presentation: In this paper, we present the case of male 40-year-old presented with complaints of pain and defective vision in the right eye. Visual examination of the right eye is 1/ . It was found, palpebral edema, hyperemic tarsal conjunctiva. The bulbar conjunctiva showed conjunctival injection, ciliary injection. The cornea looks completely cloudy, the surface is not slippery, infiltrates and edema. The patient was treated with medical and surgical therapy, and then the patient’s have a good clinical response and was able to return to work. Conclusion: Indonesian farmers have highrisk of fungal corneal ulcers. Fungal corneal ulcers is important cause of corneal blindness all over the world especially in develoving countries. Fungal corneal ulcers can diagnosis by slitlamp biomicroscopic examination and culture are essential for early specific diagnosis and must be taken consideratiaon to establish the most effective treatment and avoid severe complications. Keywords: Fungal Corneal Ulcers, Blindness, Optimal Treatment of Corneal Ulcers, Tissue Discontinuity